2019
DOI: 10.3390/ijms20235965
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Signatures of the JC Polyomavirus in Paired Normal and Altered Colorectal Mucosa Indicate a Link with Human Colorectal Cancer, but Not with Cancer Progression

Abstract: The JC polyomavirus (JCV) has been repeatedly but discordantly detected in healthy colonic mucosa, adenomatous polyps, and colorectal cancer (CRC), and proposed to contribute to oncogenesis. The controversies may derive from differences in JCV targets, patient’s cohorts, and methods. Studies of simultaneous detection, quantification, and characterization of JCV presence/expression in paired samples of normal/altered tissues of the same patient are lacking. Therefore, we simultaneously quantified JCV presence (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…The results presented here highlight the need for further studies investigating HPyV2 contamination in the human population and in the water sources of the studied municipalities as the presence of this human-specific viral marker is highly indicative of poor water quality, especially when we consider that this virus can be linked with human colorectal cancer [29][30][31] or even undergo reactivation in immunosuppressed individuals, who have a high risk of developing PML [32].…”
Section: Discussionmentioning
confidence: 81%
“…The results presented here highlight the need for further studies investigating HPyV2 contamination in the human population and in the water sources of the studied municipalities as the presence of this human-specific viral marker is highly indicative of poor water quality, especially when we consider that this virus can be linked with human colorectal cancer [29][30][31] or even undergo reactivation in immunosuppressed individuals, who have a high risk of developing PML [32].…”
Section: Discussionmentioning
confidence: 81%
“…Colorectal cancer (CRC) is the most common cancer of the gastrointestinal tract, with approximately two million new cases estimated in 2020 worldwide [57]. CRC is a well-studied malignancy for which extensive and heterogeneous genomic aberrations, well-defined risk factors, slow progression, and identifiable and treatable preneoplastic lesions have been described [58,59]. Recent data have also validated the significant role of epigenetics in regulating the function of CRC cells [60][61][62].…”
Section: Durvalumab Plus Tremelimumab In Gastrointestinal Tumorsmentioning
confidence: 99%
“…Recent reports have demonstrated the presence of HPV16 [13] and HPV18 [14] DNA or antigen in clinical colorectal samples indicating the possible risk of HPV in CRC. Similarly, JCV being an opportunistic pathogen, is distinctly present in the gastrointestinal tract and remains latent in various organs such as kidneys, and B-lymphocytes [15] . Studies by Mou et al [16] revealed the persistent association between JCV and colorectal tumor samples while Ksiaa et al [17] manifested its tumorigenic role.…”
Section: Introductionmentioning
confidence: 99%